Fuad Buleibl’s Social Poetry A Literary And Artistic Study/ الشعر الاجتماعي عند فؤاد بُليبل دراسة أدبية وفنية - Abdulkader Saleh Badlah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study examines the social poetry of Fuad Bleybel as a literary production that combines aesthetic sensitivity with social awareness. It moves beyond theoretical description to a semantic analysis of Bleybel’s poetry, which reflects the reality of society in his time and the afflictions that plagued it. The first part of the study discusses the concept and historical development of social poetry, while the second, applied part analyzes Bleybel’s social poetry from artistic and literary perspectives. From an artistic standpoint, the study explores elements such as imagination, figurative imagery, techniques of personification and embodiment, the poetic narrative, language, musical rhythm, and the sincerity of emotion. From a literary standpoint, it addresses the social reality and its positive aspects humility, benevolence, and kindness to the weak—as well as its negative aspects oppression, tyranny, hunger, misery, and disloyalty—alongside themes of education and unity. The study concludes with the most significant findings.